Shared decision-making and interprofessional collaboration in mental healthcare: a qualitative study exploring perceptions of barriers and facilitators. Issue 5 (16th May 2013) - Chong, Wei Wen; Aslani, Parisa; Chen, Timothy F.
Abstract: Shared decision-making and interprofessional collaboration are important approaches to achieving consumer-centered care. The concept of shared decision-making has been expanded recently to include the interprofessional healthcare team. This study explored healthcare providers' perceptions of barriers and facilitators to both shared decision-making and interprofessional collaboration in mental healthcare. Semi-structured interviews were conducted with 31 healthcare providers, including medical practitioners (psychiatrists, general practitioners), pharmacists, nurses, occupational therapists, psychologists and social workers. Healthcare providers identified several factors as barriers to, and facilitators of shared decision-making that could be categorized into three major themes: factors associated with mental health consumers, factors associated with healthcare providers and factors associated with healthcare service delivery. Consumers' lack of competence to participate was frequently perceived by mental health specialty providers to be a primary barrier to shared decision-making, while information provision on illness and treatment to consumers was cited by healthcare providers from all professions to be an important facilitator of shared decision-making. Whilst healthcare providers perceived interprofessional collaboration to be influenced by healthcare provider, environmental and systemic factors, emphasis of the factors differed among healthcare providers. To facilitate interprofessional collaboration, mental health specialty providers emphasized the importance of improving mental health expertise among general practitioners and community pharmacists, whereas general health providers were of the opinion that information sharing between providers and healthcare settings was the key. The findings of this study suggest that changes may be necessary at several levels (i.e. consumer, provider and environment) to implement effective shared decision-making and interprofessional collaboration in mental healthcare.